Visco-thermoelastic rectangular plate under uniform loading: A study of deflection - Chopra Deepti; Singh Prince (Nonlinear Engineering, 2025)
Examining the deflection properties while designing and analyzing structural elements offers important information about working of visco-thermoelastic plates in microelectromechanical systems, sensors, and flexible electronic systems. The aim of the current study is to increase the stability and durability in heat-sensitive situations. This study focuses on the transverse deflection in a homogeneous, isotropic, visco-thermoelastic rectangular plate under the influence of uniform loading. The edges of plate are considered at different boundary conditions. Boundary conditions can either involve all edges being simply supported or keeping them simply supported and clamped alternatively. The deflection analysis utilizes the Laplace transform and Finite Fourier sine transform. Inverse Laplace transform is resolved using residue method. MATLAB software aids numerical computation of deflection expression post-Inverse Laplace Transform. Graphical analysis explores the diverse boundary conditions across different modes. The variation in deflection has been studied in the plate under varied circumstances. The findings provide useful insights for engineering applications involving thermal and mechanical stability and advance theoretical and computational understanding of deflection dynamics in visco-thermoelastic rectangular plates under uniform loads.